Could local surgery improve survival in de novo stage IV breast cancer? - Xiong, Zhenchong (BMC Cancer, 2018)
BACKGROUND: Resection of the primary tumor is recommended for symptom relief in de novo stage IV breast cancer. We explored whether local surgery could provide a survival benefit in these patients and attempted to characterize the population that could benefit from surgery. METHODS: Metastatic Breast cancer patients (N = 313) with intact primary tumor between January 2006 and April 2013 were separated into two groups according to whether or not they had undergone surgery. The difference in characteristics between the two groups was analyzed using chi-square test, Fisher’s exact test and Mann-Whitney test. Univariable and multivariable Cox regression and stratified survival analysis were used to assess the effect of surgery on survival. RESULTS: Of the 313 patients, 188 (60.1%) underwent local surgery. Patients with local surgery had a 47% reduction in mortality risk vs. those with no surgery (median survival 78 months vs. 37 months; HR = 0.53; 95% CI, 0.36–0.78) after adjustment for clinical and tumor characteristics. Stratified survival analysis showed that patients with bone metastasis alone (and primary tumor ≤5 cm), soft tissue metastasis, or ≤ 3 metastasis sites benefit from surgery. CONCLUSION: Surgical resection of the primary tumor can improve survival in selected de novo stage IV breast cancer patients.